A self-powered photoelectrochemical sensor and its preparation method and application
By developing a self-energized photoelectrochemical sensor, using photoelectrodes and molecular imprinted films composed of WO3/TiO2 and C/MoS2/Au nanoparticles, the complex and time-consuming problem of detecting chloroquine phosphate in the prior art is solved, and an efficient, simple and green detection method is achieved.
Patent Information
- Application Number
- CN202210939189.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-08-05
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2042-08-05
AI Technical Summary
There is a lack of a simple, fast and efficient method for detecting chloroquine phosphate in the prior art. The traditional method is complex in operation, time-consuming and expensive in equipment.
A self-energized photoelectrochemical sensor was developed, including a photoanode and a photocathode, which consists of a mixture of WO3 and TiO2, and a photocathode consists of C/MoS2 and Au nanoparticles, and a molecular imprint film specifically identifying chloroquine phosphate on its surface.
It realizes miniaturization, simplification, strong specificity and high sensitivity detection. The sensor does not require additional energy, is green and environmentally friendly, has a wide detection range and low detection limit, and is suitable for rapid online detection of clinical serum and water bodies.
Smart Images

Figure CN115372443B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of photoelectrochemical sensors, and in particular relates to a self-powered photoelectrochemical sensor and a preparation method and application thereof. Background Art
[0002] Whether it is controlling the dosage of medicines during treatment or controlling drug contamination in medical wastewater, sensitive detection of chloroquine phosphate has great practical significance.
[0003] At present, the main methods for detecting chloroquine phosphate are: enzyme-linked immunosorbent assay, gas-liquid chromatography, fluorescence analysis, electrochemical analysis, etc. Although these traditional methods are highly sensitive and specific, they all have some obvious disadvantages, such as: the need to train professional technicians, complex operation procedures, long time consumption, large and expensive instruments and equipment, etc. Summary of the invention
[0004] Based on the lack of a simple, rapid and efficient method for detecting chloroquine phosphate in the prior art, the present invention provides a self-powered photoelectrochemical sensor and a preparation method and application thereof.
[0005] The self-powered photoelectrochemical sensor provided by the present invention has the characteristics of miniaturization, simplification, strong specificity and high sensitivity. At the same time, the preparation method of the self-powered photoelectrochemical sensor proposed by the present invention is simple and convenient, and the raw materials used are easy to obtain and inexpensive. The obtained sensor does not need to add other energy sources, is green and environmentally friendly, and can be recycled and mass-produced, and has good practical application prospects. The sensor proposed by the present invention can be used for the detection of chloroquine phosphate, and has a wider detection range and a lower detection limit than the traditional detection method.
[0006] To achieve the aforementioned object of the invention, the present invention can be implemented through the following technical solutions:
[0007] The present invention first provides a self-powered photoelectrochemical sensor, comprising a photoanode, a photocathode and an electrolyte.
[0008] The photoanode includes a substrate on which WO is coated. 3 With TiO 2 mixture of
[0009] The photocathode comprises a substrate on which a C / MoS 2 , in C / MoS 2 Au nanoparticles are deposited on the surface, and a molecular imprinting film that specifically recognizes chloroquine phosphate is formed on the surface of the photocathode.
[0010] In one embodiment of the invention, the electrolyte is 0.1 M phosphate buffer, pH 7.4.
[0011] In one embodiment of the present invention, WO 3 and TiO 2 The amount of substance ratio is 1:19.
[0012] In one embodiment of the present invention, the WO 3 It is a hollow spherical structure.
[0013] In one embodiment of the present invention, the molecular imprinting membrane that specifically recognizes chloroquine phosphate is prepared by the following method: using chloroquine phosphate as a template molecule to initiate the self-polymerization reaction of o-phenylenediamine on the surface of the photocathode to synthesize the molecular imprinting membrane that specifically recognizes chloroquine phosphate.
[0014] In one embodiment of the present invention, the substrate is a FTO substrate.
[0015] The present invention further provides a method for preparing a self-powered photoelectrochemical sensor, comprising the following steps:
[0016] (1) Will WO 3 and TiO 2 After mixing, the photoanode WO was obtained by spin coating on the FTO substrate. 3 / TiO 2 / FTO;
[0017] (2) C / MoS 2 Drop coating on FTO, using electrodeposition technology, on C / MoS 2 Au nanoparticles (AuNPs) were deposited on the surface to obtain the photocathode Au NPs / C / MoS 2 / FTO;
[0018] (3) using electrochemical methods, chloroquine phosphate was used as a template molecule to initiate the self-polymerization reaction of o-phenylenediamine on the surface of the photocathode to synthesize a molecularly imprinted membrane modified electrode;
[0019] The photoanode, photocathode and electrolyte constitute a self-powered photoelectrochemical sensor.
[0020] In one embodiment of the present invention, the Oswald ripening reaction principle is used to convert WCl 6 Preparation of hollow spherical WO by hydrothermal reaction in acetic acid 3 .
[0021] In one embodiment of the present invention, WCl is vigorously stirred at room temperature. 6 The acetic acid solution was added for 1 h, and then the solution was kept at 180 ° C for 12 h of hydrothermal reaction, and then the product was annealed in a muffle furnace to obtain hollow spherical WO 3 Nanomaterials.
[0022] In one embodiment of the present invention, TiO 2 .
[0023] In one embodiment of the present invention, sodium fluoride is added to a sulfuric acid solution of tetrabutyl titanate, and after stirring at room temperature for 1 hour, the mixed solution is kept at 180°C for 24 hours of hydrothermal reaction, and after cooling to room temperature, centrifuged, washed alternately with ethanol and deionized water three times, and then vacuum dried to obtain TiO 2 .
[0024] In one embodiment of the present invention, in step (1), WO 3 and TiO 2 The amount of substance ratio is 1:19.
[0025] In one embodiment of the present invention, in step (2), C / MoS 2 CTAB / MoS 2 Prepared by calcination. Calcination allows CTAB to generate carbon in situ and embed it into MoS 2 C / MoS 2 .
[0026] In one embodiment of the present invention, in step (2), CTAB / MoS is prepared hydrothermally using ammonium molybdate tetrahydrate, thiourea and cetyltrimethylammonium bromide (CTAB). 2 Then, nitrogen calcination was used to generate carbon embedded in MoS in situ by CTAB. 2 C / MoS 2 .
[0027] In one embodiment of the present invention, a hexadecyl trimethyl ammonium bromide solution is first slowly added to an ammonium molybdate tetrahydrate solution, and then the mixture is added to a thiourea solution for a hydrothermal reaction to prepare CTAB / MoS 2 .
[0028] In one embodiment of the present invention, in step (2), the hydrothermal reaction is carried out at 250° C. for 12 hours.
[0029] In one embodiment of the present invention, in step (2), CTAB / MoS 2 The calcination conditions are: calcination at 550 °C for 2 h in a nitrogen atmosphere to prepare C / MoS 2 .
[0030] In one embodiment of the present invention, in step (2), CTAB / MoS 2 Before calcination, the samples were washed alternately with ethanol and deionized water.
[0031] In one embodiment of the present invention, in step (2), C / MoS 2 The method of drop coating on FTO is: C / MoS 2 Dispersed in isopropanol solution, then dripped into The 117 solution was ultrasonically treated for 10 min, and the mixed solution was evenly drop-coated on FTO.
[0032] In one embodiment of the present invention, in step (2), electrodeposition technology is used to deposit C / MoS 2 When Au nanoparticles (Au NPs) were deposited on the surface, the potential range was 0-1 V and the scan rate was 50 mV s -1 .
[0033] In one embodiment of the present invention, in step (2), electrodeposition technology is used to deposit C / MoS 2 When Au nanoparticles (Au NPs) were deposited on the surface, the electrolyte solution used was HAuCl 4 of deoxygenated solution.
[0034] In one embodiment of the present invention, in step (3), the specific method of synthesizing a molecularly imprinted membrane modified electrode by using an electrochemical method to initiate a self-polymerization reaction of o-phenylenediamine on the surface of a photocathode using chloroquine phosphate as a template molecule is as follows: cyclic voltammetry is performed in a three-electrode system, a potential range of 0 to 0.8 V is selected, and an Ag / AgCl electrode is used as a reference electrode.
[0035] In one embodiment of the present invention, in step (3), an electrode modified with a molecular imprinting membrane is synthesized by using an electrochemical cyclic voltammetry method, using chloroquine phosphate as a template molecule to initiate a self-polymerization reaction of o-phenylenediamine (polymer monomer) on the surface of a photocathode. When the template molecule contacts the polymer monomer, multiple action points are formed, and this action is memorized through the polymerization process. When the template molecule is removed, a hole with multiple action points that matches the spatial configuration of the template molecule is formed in the polymer, and such a hole has a selective recognition characteristic for the template molecule. The specific method is:
[0036] O-phenylenediamine (OPD) and chloroquine phosphate were dissolved in acetone buffer solution. The mixed solution was purged with nitrogen for 30 min to obtain the MIP electropolymerization solution. The NIP electropolymerization solution was prepared in the same way, but without the addition of chloroquine phosphate as a template molecule. Cyclic voltammetry was performed in a three-electrode system using Ag / AgCl as the reference electrode. The potential range of 0–0.8 V was 50 mV s -1 At a scanning rate of 30 cycles, the molecular imprinted film was modified on the photocathode Au / C / MoS 2 / FTO on.
[0037] In one embodiment of the present invention, in step (3), after obtaining the electrode modified with the molecular imprinting membrane, the original template molecule chloroquine phosphate is removed by elution to obtain a self-powered photoelectrochemical sensor, that is, a photoelectrochemical molecular imprinting sensor with specific selection for chloroquine phosphate.
[0038] In one embodiment of the present invention, in step (3), after obtaining the electrode modified with the molecular imprinting membrane, the solvent selected for eluting to remove the original template molecule chloroquine phosphate is an acetic acid:methanol mixed solution, and the volume ratio of acetic acid to methanol in the acetic acid:methanol mixed solution is 1:9.
[0039] The acetic acid:methanol mixed solution can destroy the binding between chloroquine phosphate and the polymer membrane. The removed MIP (rMIP) electrode is then obtained by repeated washing with ultrapure water and drying.
[0040] The present invention also provides an application of the self-powered photoelectrochemical sensor, which is used to detect chloroquine phosphate.
[0041] The present invention uses FTO conductive glass as a substrate to prepare WO 3 With TiO 2 The heterojunction was used as the photoanode, and the layered carbon intercalated ultra-thin molybdenum disulfide microspheres modified with electrodeposited gold nanoparticles were used as the photoanode, and a self-powered photoelectrochemical sensing system based on water / oxygen self-circulation was constructed. The system does not require external driving force and electron donor acceptor, and based on the water / oxygen cycle, it not only achieves self-power and reduces the background interference of the system. The molecular imprinting film that specifically recognizes chloroquine phosphate was synthesized on the photocathode by initiating the polymerization reaction of o-phenylenediamine through electrochemical technology. Using simulated sunlight as the excitation light source, the concentration of chloroquine phosphate was detected using it technology on the CHI-660e workstation.
[0042] The application of the self-powered chloroquine phosphate molecular imprinting sensor based on the fuel-free photoelectrochemical cell of the present invention has the following advantages: the photoelectrochemical response is sensitive and the detection range is wide, which can be 1×10 -6 ~1×10 -3 The detection can be carried out within the concentration range of M, and the anti-interference ability is strong; and the preparation method of the invention is simple, rapid and low-cost, and can be applied to the rapid online detection of clinical serum and water.
[0043] Compared with the prior art, the solution of the present invention has the following effects:
[0044] 1. The sensor is based on a fuel-free photoelectrochemical cell to achieve the goal of self-powered, realizing a design without a membrane or a dielectric. It converts solar energy into electrical energy through chemical energy without the need for additional fuel, which is very environmentally friendly.
[0045] 2. This sensor also overcomes the problems of general self-powered sensors that use biocatalysts, resulting in instability, loss of activity, harsh detection conditions and high costs.
[0046] 3. The material preparation method required to construct the sensor is simple, and only simple reaction conditions are required during the experiment. The constructed sensor has a fast response speed and is easy to operate, without the need for other large instruments and professionals. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0048] FIG1( a ) and FIG1( b ) are scanning electron microscope (SEM) images of a nanomaterial used as a sensor photoanode and a nanomaterial used as a sensor photocathode, respectively;
[0049] FIG2( a ) and FIG2( b ) are X-ray diffraction (XRD) patterns of the nanomaterial used as the sensor photoanode and the nanomaterial used as the sensor photocathode, respectively;
[0050] FIG3( a ) and FIG3( b ) are full X-ray photoelectron spectroscopy (XPS) spectra of the nanomaterial used as the sensor photoanode and the nanomaterial used as the sensor photocathode, respectively;
[0051] FIG4( a ) and FIG4( b ) are ultraviolet-visible diffuse reflectance absorption spectra (UV-vis DRS) of the nanomaterial used as the sensor photoanode and the nanomaterial used as the sensor photocathode, respectively;
[0052] Figure 5 It is the power density and VI curve of the sensor;
[0053] Figure 6(a) is a quantitative analysis IT diagram of the sensor, and Figure 6(b) is a linear regression curve diagram;
[0054] FIG7( a ) is a selectivity test diagram of the sensor, and FIG7( b ) is a corresponding interfering substance structural formula;
[0055] FIG8( a ) is a stability test diagram of the sensor, and FIG8( b ) is a reproducibility test diagram of the sensor.
[0056] Fig. 9 Schematic diagram of the principle of a self-powered photoelectrochemical sensor. DETAILED DESCRIPTION
[0057] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0058] Experimental reagents of the present invention:
[0059] Ammonium molybdate tetrahydrate, hexadecyltrimethylammonium bromide, thiourea, methanol, sodium fluoride, tungsten hexachloride, tetrabutyl titanate, and chloroquine phosphate were purchased from Shanghai McLean Biochemical Co., Ltd. O-phenylenediamine was purchased from Shanghai Aladdin Reagent Co., Ltd. Acetic acid, ethanol, acetic acid sulfuric acid, and acetone were purchased from Shanghai Titan Technology Co., Ltd. Isopropanol was purchased from Shanghai McLean Biochemical Co., Ltd. Chloroauric acid was purchased from Shanghai Yian Chemical Co., Ltd. 117 solution was purchased from Sigma Aligma. FTO conductive glass was purchased from Zhuhai Kaiwei Optoelectronics Technology Co., Ltd. The water used in the experiment was deionized water (18.2 MΩ). All chemical reagents were of analytical grade and used directly without further purification.
[0060] The product prepared by the present invention is characterized by the following means: the morphology of the sample is analyzed by scanning electron microscopy obtained by a Japanese HITACHI S-4800 scanning electron microscope. The structure is analyzed by a Rigaku D / Max-RB X-ray diffractometer (XRD). The elemental composition of the sample is analyzed by a Thermo Scientific K-Alpha X-ray photoelectron spectrometer. The light absorption range and light absorption intensity of the sample are analyzed by ultraviolet visible diffuse reflectance spectrum obtained on a Shimadzu UV-2450 diffuse reflectometer. The electrochemical performance and analytical performance test of the sensor are performed by a CHI-660e electrochemical workstation.
[0061] 1.WO 3 / TiO 2 Preparation of FTO photoanode
[0062] 0.811 g of WCl 6 Dissolve in acetic acid, stir vigorously at room temperature for 1h, transfer the solution to a 100mL hydrothermal reactor, react at 180℃ for 12h; after cooling to room temperature, centrifuge, wash alternately with ethanol and deionized water three times, and then vacuum dry. The dried product is annealed at 500℃ in a muffle furnace for 1h to obtain WO 330 mmol of tetrabutyl titanate was dissolved in 2.0 M sulfuric acid, and 10 mmol of sodium fluoride was added. After stirring for 1 hour, the solution was transferred to a 100 mL hydrothermal reactor and reacted at 180 ° C for 24 hours. After cooling to room temperature, centrifugation was performed, and TiO was obtained after washing with ethanol and deionized water three times. 2 Cut the FTO conductive glass into 1×1.5cm 2 , and then ultrasonically cleaned with acetone, ethanol, and deionized water for 30 minutes respectively. 3 Nanoparticles and TiO 2 The nanoparticles were dispersed in isopropanol and then dropped into The 117 solution was ultrasonically treated for 10 min. The mixture was spin-coated onto the treated FTO conductive glass and vacuum dried at 70 °C to obtain WO 3 / TiO 2 / FTO photoanode.
[0063] 2. Au NPs / C / MoS 2 Preparation of FTO photocathode
[0064] 100 mg of ammonium molybdate tetrahydrate, 220 mg of hexadecyltrimethylammonium bromide and 200 mg of thiourea were dissolved in 65 mL of deionized water, stirred vigorously for 30 min, and the solution was transferred to a 100 mL hydrothermal reactor and reacted at 250 °C for 12 h. After cooling to room temperature, centrifugation was performed, and the product was washed alternately with ethanol and deionized water three times and then dried in vacuum. The obtained product was calcined at 550 °C for 2 h in a tubular furnace under nitrogen atmosphere to obtain C / MoS 2 Cut the FTO conductive glass into 1×1.5cm 2 Then, the FTO glass was cleaned with acetone, ethanol and deionized water for 30 minutes. 2 area, 10mg C / MoS 2 Disperse in 1 mL of isopropanol solution and then drip into The 117 solution was ultrasonically treated for 10 min, and 300 μL of the mixed solution was evenly dropped on the treated FTO. Cyclic voltammetry was performed in a three-electrode system using Ag / AgCl as the reference electrode. -1 At a scan rate of 4 The gold nanoparticles were deposited on the C / MoS 2 After washing with deionized water and drying at 50 °C, Au NPs / C / MoS 2 / FTO photocathode.
[0065] The obtained samples were subjected to scanning electron microscopy (SEM) analysis, X-ray diffraction (XRD) pattern analysis, X-ray photoelectron spectroscopy (XPS) and ultraviolet-visible diffuse reflectance spectroscopy (UV-vis DRS) analysis.
[0066] Figure 1(a) and Figure 1(b) are WO 3 / TiO 2 / FTO photoanode and Au NPs / C / MoS 2 Scanning electron microscope (SEM) photos of the FTO / FTO photocathode. As shown in Figure 1(a) and Figure 1(b), the synthesized electrode material has a large specific surface area and a regular structure. This is conducive to the separation of photogenerated carriers and improves the photoelectrochemical activity.
[0067] Figure 2(a) and Figure 2(b) are WO 3 / TiO 2 / FTO photoanode and Au NPs / C / MoS 2 X-ray diffraction (XRD) spectrum of the FTO photocathode. As shown in Figure 2(a) and Figure 2(b), the single material corresponds to the diffraction peaks on the standard card one by one, while the composite material also has the diffraction peaks of the single material. This proves the successful synthesis of the material and the successful construction of the heterojunction.
[0068] Figure 3(a) and Figure 3(b) are WO 3 / TiO 2 / FTO photoanode and Au NPs / C / MoS 2 / Full spectrum of X-ray photoelectron spectroscopy (XPS) of FTO photocathode. As shown in Figure 3(a) and Figure 3(b), the element types shown in the full spectrum of XPS are in very good correspondence with the theory. This also indirectly proves the successful synthesis of the material.
[0069] Figure 4(a) and Figure 4(b) are WO 3 / TiO 2 / FTO photoanode and Au NPs / C / MoS 2 UV-visible diffuse reflectance spectrum (UV-vis DRS) of WO / FTO photocathode. As shown in Figure 4(a), it can be seen that 3 / TiO 2 The light absorption of heterojunction materials in the range of 300-450nm is higher than that of the corresponding TiO 2 As shown in Figure 4(b), in the wavelength range of 300-800 nm, the C / MoS 2 Compared with the UV-Vis diffuse reflectance spectrum of Au NPs / C / MoS 2The light absorption capacity of the composite material is significantly improved. At around 550nm, an obvious characteristic absorption peak of gold nanoparticles appears. This shows that Au NPs are successfully modified and the absorption of visible light by the composite material is increased through the surface localized plasmon resonance effect.
[0070] 3. Construction of fuel-free photocatalytic cells and electrochemical performance testing
[0071] WO 3 / TiO 2 / FTO as photoanode, Au NPs / C / MoS 2 / FTO was used as the photocathode, and phosphate buffered saline solution (pH=7.4) was used as the electrolyte solution to assemble a fuel-free PEC of a dual-electrode system. When irradiated with simulated sunlight, the photoanode produces electrons and holes, and an oxygen evolution reaction of water occurs. In this process, electrons are transferred to the photocathode along the external circuit and generate photocurrent, and holes are captured to generate oxygen. The photocathode obtains electrons from the photoanode through the external circuit and reduces the oxygen generated by the photoanode. In this system, the oxidation product oxygen of the photoanode can be consumed by the photocathode as a reactant, and the reduction product water of the photocathode can also be consumed by the photoanode as a reactant, forming a water-oxygen self-circulation without the need to add any electron donor / acceptor.
[0072] The electrochemical performance of the PEC was tested using a CHI-660D electrochemical workstation under simulated sunlight.
[0073] Figure 5 The power density and VI curve of the sensor are shown in the figure. As shown in the figure, under the excitation of simulated sunlight, the open circuit voltage is 0.48V, when the output voltage is 0.28V, the output current is 61μA and shows 16.84μW·cm -2 The maximum output power.
[0074] 4. Construction of Chloroquine Phosphate MIP Sensor Based on Fuel-free Photocatalytic Cell
[0075] OPD and chloroquine phosphate were dissolved in acetone buffer solution. The mixed solution was purged with nitrogen for 30 min to obtain the MIP electropolymerization solution. The NIP electropolymerization solution was prepared in the same way, but without the addition of chloroquine phosphate as a template molecule. Cyclic voltammetry was used in a three-electrode system using Ag / AgCl as the reference electrode. The potential range of 0–0.8 V was 50 mVs -1The molecular imprinted film was modified on the photocathode Au / C / MoS2 at a scanning rate of 30 cycles. The obtained MIP-modified photocathode was immersed in a mixed solution of acetic acid: methanol (V:V = 1:9) for 10 minutes to destroy the binding between chloroquine phosphate and the polymer film. The MIP-removed (rMIP) electrode was then repeatedly washed with ultrapure water and dried.
[0076] Finally, in a single-chamber membrane-free transparent quartz photochemical cell, WO 3 / TiO 2 / FTO photoanode, rMIP / AuNPs / C / MoS 2 / FTO photocathode and 100mL 0.1M phosphate buffer solution (PBS, pH7.4) were used to construct a chloroquine phosphate MIP sensor for a fuel-free photocatalytic cell.
[0077] 5. Quantitative analysis of chloroquine phosphate by the constructed sensor
[0078] In 0.1M PBS (pH 7.4), the current-time response curve in the "on-off" mode under simulated sunlight was recorded. The quantitative relationship between the photocurrent of the sensor and different chloroquine phosphate concentrations was studied. The different concentrations of chloroquine phosphate solutions in the quantitative experiment were prepared by adding a series of different concentrations of chloroquine phosphate (eg 1×10 -6 ,5×10 -6 ,1×10 -5 ,5×10 -5 ,1×10 -4 ,2×10 -4 ,5×10 -4 ,1×10 -3 M) is obtained.
[0079] Figure 6(a) is the quantitative analysis IT diagram of the sensor, and Figure 6(b) is the linear regression curve. As shown in Figure 6(a), as the concentration of chloroquine phosphate solution gradually increases, the cathode current of the sensor gradually decreases. This is because chloroquine phosphate is re-adsorbed in the specific cavity on the molecular imprinted film. Due to the large steric hindrance and low conductivity of chloroquine phosphate, the transfer of electrons on the photocathode is limited. Figure 6(b) shows the results of the experiment at 1×10 -6 ~1×10 -3 Within the concentration range of M, the linear relationship between the cathode photocurrent response decay and the logarithmic value of chloroquine phosphate concentration. The linear fitting curve is ΔI = -2.4756 + 2.7155logCCQP (R 2 =0.9926) and ΔI = 1.5201 + 0.3619logCCQP (R 2 =0.9921).
[0080] 6. Analytical performance of the constructed sensor for chloroquine phosphate
[0081] Select some substances that may coexist or have similar structures and groups as interfering substances for selective experiments. -1 Diclofenac sodium, sulfadiazine, sulfadimethoxine, sulfamethoxazole, dexamethasone, ribavirin and ciprofloxacin (100 times the concentration of chloroquine phosphate) were added to PBS solutions containing 100 μM chloroquine phosphate, and the cathode photocurrent response of the sensor in different solutions was recorded. In order to explore the stability of the constructed self-powered sensor, the sensor was cycled "on-off" for 500 s under simulated sunlight. Six batches of self-powered fuel-free PEC sensors were prepared in the same way to explore the reproducibility of the scheme.
[0082] Figure 7(a) is the selectivity test diagram of the sensor, and Figure 7(b) is the corresponding interfering compound structure. In the presence of ultra-high concentrations of interfering compounds, the cathode photocurrent response did not change significantly, indicating that the proposed self-powered fuel-free PEC sensor has a high specificity for the detection of chloroquine phosphate.
[0083] Figure 8(a) is a stability test diagram of the sensor, and Figure 8(b) is a reproducibility test diagram of the sensor. As shown in Figure 8(a), the photocurrent of the self-powered fuel-free PEC sensor is very stable during the cycle. As shown in Figure 8(b), the cathode photocurrent responses of sensors from different batches are almost the same. The results show that the prepared sensor has good reproducibility.
[0084] VII. Analysis of chloroquine phosphate in actual samples by the constructed sensor
[0085] Chloroquine phosphate was added to human serum and river water samples by standard addition method, and the constructed PEC sensor was used to detect the content of chloroquine phosphate in real samples. The recovery rate in human serum samples was 96.8-102.1%, with RSD of 1.32-4.20%, and the recovery rate in river water samples was 94.3-106.3%, with RSD of 1.66%-5.13%. The experimental results show that the constructed self-powered fuel-free PEC sensor is reliable for actual sample analysis and has good practicality and applicability in both clinical monitoring and environmental detection.
[0086] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A self-powered photoelectrochemical sensor, characterized in that: It includes a photoanode, a photocathode and an electrolyte. The photoanode includes a substrate, on which a mixture of WO3 and TiO2 is coated; The photocathode comprises a substrate, C / MoS2 is coated on the substrate, Au nanoparticles are deposited on the surface of the C / MoS2, and a molecular imprinting film for specifically recognizing chloroquine phosphate is formed on the surface of the photocathode.
2. A self-powered photoelectrochemical sensor according to claim 1, characterized in that: The molar ratio of WO3 and TiO2 is 1:
19.
3. A self-powered photoelectrochemical sensor according to claim 1, characterized in that: The molecular imprinting membrane for specifically recognizing chloroquine phosphate is prepared by the following method: using chloroquine phosphate as a template molecule to initiate a self-polymerization reaction of o-phenylenediamine on the surface of a photocathode to synthesize the molecular imprinting membrane for specifically recognizing chloroquine phosphate.
4. The method for preparing the self-powered photoelectrochemical sensor according to any one of claims 1 to 3, characterized in that: The following steps are involved: (1) WO3 and TiO2 were mixed and then spin-coated on a FTO substrate to obtain a photoanode WO3 / TiO2 / FTO; (2) C / MoS2 was drop-coated on FTO, and Au nanoparticles were deposited on the surface of C / MoS2 using electrodeposition technology to obtain the photocathode Au NPs / C / MoS2 / FTO; (3) using electrochemical methods, chloroquine phosphate was used as a template molecule to initiate the self-polymerization reaction of o-phenylenediamine on the surface of the photocathode to synthesize a molecularly imprinted membrane modified electrode; The photoanode, photocathode and electrolyte constitute a self-powered photoelectrochemical sensor.
5. The method for preparing the self-powered photoelectrochemical sensor according to claim 4, characterized in that: The acetic acid solution of WCl6 was vigorously stirred at room temperature for 1 h, and then the solution was kept at 180°C for 12 h of hydrothermal reaction. The product was then annealed in a muffle furnace to obtain hollow spherical WO3 nanomaterials.
6. The method for preparing the self-powered photoelectrochemical sensor according to claim 4, characterized in that: Sodium fluoride was added to the sulfuric acid solution of tetrabutyl titanate, and after stirring at room temperature for 1 hour, the mixed solution was kept at 180°C for 24 hours of hydrothermal reaction. After cooling to room temperature, it was centrifuged, washed alternately with ethanol and deionized water three times, and then vacuum dried to obtain TiO2.
7. The method for preparing the self-powered photoelectrochemical sensor according to claim 4, characterized in that: In step (2), CTAB / MoS2 is hydrothermally prepared using ammonium molybdate tetrahydrate, thiourea and hexadecyltrimethylammonium bromide, and then calcined with nitrogen to generate carbon in situ from CTAB and embed it into MoS2 to form C / MoS2.
8. The method for preparing the self-powered photoelectrochemical sensor according to claim 4, characterized in that: In step (2), when Au nanoparticles are deposited on the surface of C / MoS2 using electrodeposition technology, the potential selection range is 0-1V and the scanning rate is 50mVs -1 ; When Au nanoparticles were deposited on the surface of C / MoS2 using the electrodeposition technique, the electrolyte solution used was a deoxygenated solution of HAuCl4.
9. The method for preparing the self-powered photoelectrochemical sensor according to claim 4, characterized in that: In step (2), in step (3), the specific method of synthesizing the molecular imprinting membrane modified electrode by using an electrochemical method to initiate the self-polymerization reaction of o-phenylenediamine on the surface of the photocathode using chloroquine phosphate as a template molecule is as follows: cyclic voltammetry is performed in a three-electrode system, a potential range of 0 to 0.8 V is selected, and an Ag / AgCl electrode is used as a reference electrode.
10. Use of the self-powered photoelectrochemical sensor according to any one of claims 1 to 3, characterized in that: The self-powered photoelectrochemical sensor is used to detect chloroquine phosphate.